Studies on nano composites of SPEEK/ethylene glycol/cellulose nanocrystals as promising proton exchange membranes - Bano, Saleheen; Negi, Yuvraj S.; Illathvalappil, Rajith; Kurungot, Sreekumar; Ramya, K. (Electrochimica Acta, 2019)
The present work deals with fabrication and characterisations of nano-composite membranes composed of sulfonated poly (ether ether ketone) (SPEEK) cross-linked and reinforced with ethylene glycol (EG) and cellulose nanocrystals (CNCs) respectively. The thin films of cross-linked composite membranes were prepared by solvent casting method and further analysed for physicochemical and electrochemical properties to execute their applicability as promising proton exchange membrane (PEM) in fuel cells. The process of cross-linking helps to improve the strength and dimensional stability of bare SPEEK membranes without compromising with conductivity. However, presence of CNCs further improves the strength and provides an effective pathway for the conduction of protons in membranes by interacting through their surface hydroxyl and sulfonic acid groups with ionic moieties of polymer matrix. All prepared composite membranes showed good oxidative and thermal stability along with good proton conductivity. The cross-linked SPEEK membranes with 4 wt% loading of CNCs possess an appreciable proton conductivity of 0.186 S/cm at 95 degrees C and 95% RH which is comparable to Nafion 117. From the view point of above studies, the prepared nano-composite can be described as promising proton exchange membrane for fuel cells. (c) 2018 Elsevier Ltd. All rights reserved.
Keywords: Cellulose nanocrystals; Cross-linked SPEEK; fuel cell; oxidative stability; proton conductivity

Chemically gradient hydrogen-bonded organic framework crystal film - Mohammed, Abdul Khayum; Raya, Jesus; Pandikassala, Ajmal; Addicoat, Matthew A.; Gaber, Safa; Aslam, Mohamed; Ali, Liaqat; Kurungot, Sreekumar; Shetty, Dinesh (Angewandte Chemie-International Edition, 2023)
Hydrogen-bonded organic frameworks (HOFs) are ordered supramolecular solid structures, however, nothing much explored as centimetre-scale self-standing films. The fabrication of such crystals comprising self-supported films is challenging due to the limited flexibility and interaction of the crystals, and therefore studies on two-dimensional macrostructures of HOFs are limited to external supports. Herein, we introduce a novel chemical gradient strategy to fabricate a crystal-deposited HOF film on an in situ-formed covalent organic polymer film (Tam-Bdca-CGHOF). The fabricated film showed versatility in chemical bonding along its thickness from covalent to hydrogen-bonded network. The kinetic-controlled Tam-Bdca-CGHOF showed enhanced proton conductivity (8.3x10(-5) S cm(-1)) compared to its rapid kinetic analogue, Tam-Bdca-COP (2.1x10(-5) S cm(-1)), which signifies the advantage of bonding-engineering in the same system.
Keywords: Chemical Gradience; Crystal Films; Free-Standing Films; hydrogen-bonded organic framework; Interfacial Chemistry; proton conductivity

Unlocking the potential of proton conductivity in guanidinium-based ionic covalent organic nanosheets (iCONs) through pore interior functionalization - Kumar, Sushil; Hu, Jiahui; Pandikassala, Ajmal; Kurungot, Sreekumar; Addicoat, Matthew A.; Szekely, Gyorgy (Applied Materials Today, 2023)
Recently, scientists have been exploring the incorporation of proton carriers such as water and phosphoric acid (PA) into the pores and channels of porous materials to enhance proton conduction performance. Ionic covalent organic nanosheets (iCONs) have been identified as promising functional materials due to their inbuilt ionic interfaces, which can facilitate strong interaction with counter ions present inside the pore structure and thus shorten ion transport pathways. However, there is a lack of research related to proton conductivity in iCONs loaded with PA. To address this, we prepared three functionalized guanidinium-based iCONs using a solvothermal condensation reaction between guanidinium amine (TG) and functionalized terephthaldehyde (Da, Dha, and Dma). PA was also incorporated into the iCON structure via ex situ loading to observe its effects on proton conduction performance. The results showed that both the iCONs and PA-iCONs were highly stable in water, organic solvents, acidic and basic media. Amongst these PA-iCONs, one with hydroxyl-functionalization (PA-DhaTG) displayed high proton conductivity at 90 degrees C and 95% relative humidity due to a Grotthuss mechanism for protons. These functionalized guanidinium-based iCONs could prove useful for applications in energy conversion devices.
Keywords: chemical stability; Functionalized pore interior; Guanidinium group; ionic covalent organic nanosheets; proton conductivity

Enhancing proton conductivity of MOF-808 framework through post-functionalization with an organic salt - Pathak, Chayanika; Puthiyaveetil, Priyanka Pandinhare; Das, Sarbani; Kurungot, Sreekumar; Seth, Saona (Journal of Solid State Chemistry, 2026)
We report the role of exposed metal sites and their post-functionalization through grafting an organic salt with hydrogen bond donor and acceptor functionalities on proton conduction property of MOF-808 framework. Activation by exchange with proper solvents followed by evacuation creates a high density of coordinatively unsaturated zirconium metal sites resulting in a consistent proton conductivity of 5.6 & times; 10-5 S cm-1 at 90 degrees C and 95% relative humidity for MOF-808. Further, grafting of an organic salt 1,3-Bis(4-carboxyphenyl)imidazolium chloride (ImCl) onto the exposed metal sites yields MOF-808-ImCl, which exhibits significantly improved proton conductivity of 1.7 & times; 10-3 S cm-1.
Keywords: activation; Metal-organic framework; Post-functionalization; proton conductivity